Human Resource Management Training In The Digital Era For Dawuhan Tourism Village Managers - Frans Assa, Adrie; Johanis Rumambi, Freddy; Adinirekso, Gidion; Widjaja, Daniel; Umarudin, Umarudin (CV. Inara, 2024)
Awareness of becoming a Disaster Resilient Society encourages people to increase their preparedness for the threat of disasters and increase income from this awareness by creating the Dawuhan tourist village. Dawuhan Village, Wanayasa District, Banjarnegara Regency, Central Java has extraordinary potential for the natural environment, community and village government working together to develop the village's potential. This ongoing community service has produced a significant impact on managers and employees as well as the community around the tourist village area. This training aims to provide practical skills and knowledge needed by managers and employees to manage tourist villages well. As a result of implementing these community service activities, managers and employees are very enthusiastic about being involved in increasing the capacity and competence of managers and employees for the development and progress of tourist villages.